Review of the Southern Ocean Sanctuary: Marine Protected Areas in the context of the International Whaling Commission Sanctuary Programme - Zacharias, Mark A.; Gerber, Leah R.; Hyrenbach, K. David (J. Cetacean Res. Manage., 2023)
This scientific review of the Southern Ocean Sanctuary (SOS) was commissioned by the IWC Scientific Committee and presented to the IWC Steering Committee on 27-28 June 2004. This review addresses a number of questions related to the effectiveness of the SOS and provides recommendations on how to incorporate Marine Protected Area (MPA) concepts into the SOS and the IWC Sanctuary programme. Overall, the SOS – and IWC Sanctuaries in general – are based on vague goals and objectives that are difficult to measure, lack a rigorous approach to their design and operation and do not have an effective monitoring framework for evaluation. In particular, the SOS represents a ‘shotgun’ approach to conservation, whereby a large area is protected with little apparent rationale for boundary selection and management prescriptions within the sanctuary. While a vast array of ecosystem-level and precautionary conservation benefits have been invoked for the establishment of the SOS, in reality this sanctuary does little more than provide a false sense of security by assuming that broad protections for whale populations are in place. The SOS was designed to restrict commercial harvests from the low latitude feeding grounds occupied by large whales during the austral summer. However, the SOS does not protect against or mitigate other threats to Southern Ocean whale stocks and the marine ecosystems upon which these populations depend, including pollution, habitat degradation and loss, introduced species and global climate change. We thus contend that sanctuary establishment and evaluation should be guided by a series of measurable and tangible goals, aimed at quantifying the status of both the ‘protected’ species under consideration and their role in the broader marine ecosystem. In particular, the SOS could be improved substantially to become an important part of IWC management and the larger conservation of Southern Ocean marine ecosystems, if the following steps were implemented: (a) development of formally stated goals (e.g. biodiversity protection, fisheries enhancement); (b) establishment of measurable objectives with which to assess progress towards attaining these goals; (c) creation of a formal management plan, including the establishment of a monitoring framework; and (d) development of more appropriate review criteria, reflecting the ecological objectives of the management plan.